2013
DOI: 10.1111/jocn.12175
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about medications and products to prevent and treat pressure ulcers: a cross‐sectional survey of nurses and physicians in a Primary Health Care setting

Abstract: The data demonstrated that nurses have sufficient knowledge and skill to provide wound care and could safely write these prescriptions, although Spanish law permitting nurse prescription is not fully implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
2
2
1
Order By: Relevance
“… 20 Although the majority of nurses mentioned that the type of dressing should be selected on the basis of the characteristics of the ulcer, 20 only 34.4% of nurses understood the features of various wound dressings and had an in-depth understanding of the correct use of wound dressings based on different types of PI wounds in our study. This result is inconsistent with the results among nurses working in primary care settings, 31 which suggested that approximately 80% of those nurses knew about the correct usage of foam, alginate, hydrocolloid, and silver dressing. 31 A possible reason for this finding is that nurses require more knowledge to give prescriptions.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“… 20 Although the majority of nurses mentioned that the type of dressing should be selected on the basis of the characteristics of the ulcer, 20 only 34.4% of nurses understood the features of various wound dressings and had an in-depth understanding of the correct use of wound dressings based on different types of PI wounds in our study. This result is inconsistent with the results among nurses working in primary care settings, 31 which suggested that approximately 80% of those nurses knew about the correct usage of foam, alginate, hydrocolloid, and silver dressing. 31 A possible reason for this finding is that nurses require more knowledge to give prescriptions.…”
Section: Discussioncontrasting
confidence: 57%
“…This result is inconsistent with the results among nurses working in primary care settings, 31 which suggested that approximately 80% of those nurses knew about the correct usage of foam, alginate, hydrocolloid, and silver dressing. 31 A possible reason for this finding is that nurses require more knowledge to give prescriptions. Legalization of prescription by nurses is increasing worldwide.…”
Section: Discussioncontrasting
confidence: 57%
“…Frente a este resultado se ratifica lo concluido por Romero y cols. en su estudio "Las enfermeras tienen conocimientos suficientes y experiencia directa en úlceras por presión y cuidado de úlceras, es deseable que tanto las enfermeras como los médicos tengan entrenamiento regular para mejorar y actualizar el conocimiento de las mejores prácticas y tratamientos" (10), sustentado en que el profesional de enfermería tiene un juicio para la planificación, organización, motivación y control de la provisión de cuidados oportunos, continuos, seguros e integrales en la atención en salud de las personas, basados en la evidencia científica y demostrando su capacidad para cambiar de forma favorable el curso de la enfermedad o la mejora de las condiciones de salud de la población (11). Otra de las variables clínicas en las cuales se encontraron diferencias estadísticas es el área de la úlcera.…”
Section: Evento Epitelización Hr Punclassified
“…In a study of emergency care professionals in Spain (Hinojosa‐Caballero, ), just 23% considered their university education about PU prevention to be “good,” and the rate decreased to 19% when asked about aspects of PU treatment. Other studies have reported that 25% of nurses reported never having received any specific information about PUs in their professional program (Zamora Sánchez, ), 53.1% received no training specific to PU wound care (Romero‐Collado et al., ), and 70% indicated they did not receive sufficient education about chronic wounds in their basic nursing education program (Ayello, Baranoski & Salati, ). These deficiencies were also observed in textbooks recommended by nursing educators (Wilborn, Halfens & Dassen, ), and wide variation in PU‐related textbook content has been reported (Ayello & Meaney, ).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic wounds are a major factor in morbidity, mortality, and healthcare costs (Augustin, Brocatti, Rustenbach, Schäfer & Herberger, ; Sen et al., ). On healthcare teams, nurses typically have the responsibility of caring for patients who have these wounds or are at risk for them (Caron‐Mazet, Roth, & Guillaume, ; Romero‐Collado, Homs‐Romero, & Zabaleta‐del‐Olmo, ).…”
mentioning
confidence: 99%